Pengaruh Kepadatan Populasi terhadap Pertumbuhan dan Hasil Blewah (Cucumis melo L. var. Cantalupensis) - Rajagukguk, Natalia; Turmudi, Edhi; Handajaningsih, Merakati (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2017)
Blewah (C. melo var. Cantalupensis) is one specific type of melon with fresh and fragrance arome when the fruit is ripe. Mostly the plant is grown in Java island of Indonesia. There is no research-based information about technique of cultivationof this plant, so this experiment was done to study population density to determine the optimal spacing for growth and yield of blewah. The experiment has been implemented from February 2016 until May 2016 in the experimental field of the University of Bengkulu. This study used a complete Randomized Complete Block Design with different population density treatments i.e.: plant density of 4 plants per plot of 10 m2 (plant spacing 100 cm x 250 cm); plant density of 6 plants per plot, (plant spacing 100 cm x 166 cm); plant density of 8 crops per plot (spacing of 100 cm x 120 cm); plant density of 10 plants per plot (plant spacing 100cm x 100 cm); plant density of 12 plants per plot (plant spacing 100 cm x 83 cm); plant density of 14 plants per plot (plant spacing 100 cm x 72 cm); and plant density of 16 plants per plot (plant spacing 100cm x 62 cm). Each treatment was repeated 3 times. The experiment showed that the optimal spacing for growing blewah was at population density 12 plants/10 m2 or 12,000 plant/ha, plant spacing 100 cm x 83 cm. This arrangement of plant yielded the length of plant, the number of branches, the diameter of the fruit, the plant dry weight, the weight of the fruit per plot, and fruit thickness of 224.47 cm, 3.67, 9.61 cm, 22.15 g, 7044.80 g, and 2.21 cm respectively.Keywords: blewah, Cucumis melo var. Cantalupensis, growth, plant density, yield